ANALISIS PENERIMAAN SISTEM INFORMASI AKADEMIK BERBASIS WEB MENGUNAKAN TECHNOLOGY ACCEPTANCE MODEL (TAM) DAN USABILITY STUDI KASUS PADA STTNAS YOGYAKARTA - Handayani, Trie (ReTII, 2015)
STTNAS Yogyakarta has academic information system (SiAkad ) to help academic activity for student, educative and non educative employee, so STTNAS need to know user acceptance level to SiAkad. This study is done to know variables that influence user acceptance to SiAkad and testing of factors affected SiAkad acceptance level in STTNAS environment. Technology Acceptance Model (TAM) and Usability are methods that used in this research. TAM method involves three variables. They are perceived ease of use (PEOU), perceived usefulness (PU) and attitude toward using (ATU), whereas Usability uses seven criterias such as accessibility, customization and personalization, download speed, ease of use, error, navigation, and site content. In addition, this research also uses Structural Equation Model (SEM) to analyze connection among variables that running in AMOS 7.0 and including381 questionnaires. This study shows user acceptance level to SiAkad implementation is good, PEOU and PU are factors that influence user acceptance level to SiAkad, while ATU does not affect SiAkad acceptance level based on approval testing. Moreover, usability variable that does not affect SiAkad acceptance level is error, so that user is still difficult to find information in web. This study also proposes SiAkad to apply tools online checker for improving SiAkad acceptance level.